Viral Stomatitis - V.V. Mavrutenkov (Zaslavsky O.Yu., 2015)
Stomatitis is the inflammation of the oral mucosa caused by local or systemic factors, which can involve the mucous membrane of the cheeks and lips, palate, tongue, mouth floor and gums. Most common causes of vesicles and aphthae on the oral mucosa are: trauma, infections, autoimmune processes, tumors. Idiopathic stomatitis has a special place. The article discusses stomatitis caused by the most common viral infections: herpesviruses type 1 and 2, enteroviruses, varicella herpes zoster and measles virus.